Vitamin C content in parsley leaves (Petroselinum crispum) dried by air flow at different speeds and temperatures. - Manayay Sánchez, Damián (2019)
The behavior of the vitamin C content in smooth parsley leaves after harvesting and artificial drying were determined. The fresh branches collected from the Chaclacayo horticultural farms were stripped, washed, disinfected in chlorinated water, drained and dried with air flow hot at rates of 1 and 1.5 m / s, and temperatures ranging from 20 to 50 °C; It was found that the reduction of the vitamin content in dry leaves were 22.92 and 25.75 % respectively, no statistically significant difference was shown in the interaction of temperature and air speed of drying, and the kinetics of water loss in the samples was ruled by exponential models.